Immunogenicity and protection efficacy of a Salmonella enterica serovar Typhimurium fnr, arcA and fliC mutant. Issue 3 (15th January 2021) - Zhao, Xinxin; Zeng, Xiaoli; Dai, Qinlong; Hou, Yulong; Zhu, Dekang; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhang, Shaqiu; et al.
Abstract: Salmonella enterica serovar Typhimurium is a major food-borne pathogen that can cause self-limited gastroenteritis or life-threatening invasive diseases in humans. There is no licensed S . Typhimurium vaccine for humans to date. In this study, we attempted to construct a live attenuated vaccine strain of S . Typhimurium based on three genes, namely, the two global regulator genes fnr and arcA and the flagellin subunit gene fliC . The S . Typhimurium three-gene mutant, named SLT39 (Δ fnr Δ arcA Δ fliC ), exhibited a high level of attenuation with a colonization defect in mouse tissues and approximately 10 4 -fold decreased virulence compared with that of the wild-type strain. To evaluate the immunogenicity and protection efficacy of STL39, mice were inoculated twice with a dose of 10 7 CFU or 10 8 CFU at a 28-day interval, and the immunized mice were challenged with a lethal dose of the wild-type S . Typhimurium strain one month post second immunization. Compared with mock immunization, SLT39 immunization with either dose elicited significant serum total IgG, IgG1 and IgG2a and faecal IgA responses against inactivated S . Typhimurium antigens at a comparable level post second immunization, whereas the 10 8 CFU group induced higher levels of duodenal and caecal IgA than the 10 7 CFU group. Furthermore, the bacterial loads in mouse tissues, including Peyer's patches, spleen and liver, significantly decreased in the two SLT39 immunization groups compared to those in the control group post challenge. Additionally, all mice in the SLT39 (10 8 CFU) group and 80% of the mice in the SLT39 (10 7 CFU) group survived the lethal challenge, suggesting full protection and 80% protection efficacy, respectively. Thus, the S . Typhimurium fnr, arcA and fliC mutant proved to be a potential attenuated live vaccine candidate for prevention of homologous infection.